Comprehensive treatment strategy for improving surgical resection rate of retroperitoneal sarcomas: a histology-specific approach narrative review - Garcia-Ortega, Dorian Y. (Frontiers in Oncology, 2024)
Retroperitoneal sarcoma (RPS) represents a rare and heterogeneous group of malignancies, posing significant challenges in evaluation and management. Surgery, the cornerstone of RPS treatment, critically depends on complete resection for a favorable prognosis. The extent of resection is a crucial determinant of local control and survival. This review delves into the evolution of multidisciplinary management of localized RPS, highlighting the imperative to adapt surgical strategies to tumor histology, location, and patient functional status. We explore the principles of compartmental surgery—an extended first-line approach that involves resecting adjacent viscera for wide negative margins—and its effectiveness across different histological subtypes of RPS and more limited resections for other types. Particular emphasis is placed on the heterogeneity of the disease, as various histological subtypes exhibit distinct biological behaviors. This necessitates a shift away from a one-size-fits-all treatment approach. The review analyzes the role of different surgical strategies, focusing on histological type and location. Additionally, the potential benefits of (neo)adjuvant treatments, such as radiotherapy and chemotherapy, are examined, recognizing their specific histological indications and limitations. This comprehensive review consolidates recent data on surgical strategies and complementary therapies, advocating for a personalized approach tailored to histology. As understanding of the molecular and genetic underpinnings of RPS continues to evolve, so will strategies for its effective management, underscoring the need for global collaboration among specialists in this field to enhance our collective knowledge and treatment methodologies.